Cerebral hemodynamics in patients with cirrhosis - Öncel, Çağatay; Yılmaz, Mustafa (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Cirrhosis causes a decrease in cerebral blood flow because of a hyperdynamic circulatory state. We aimed to study the cerebral hemodynamic parameters in patients with decompensated cirrhosis and their relationship to the Child–Pugh and Model for End-Stage Liver Disease (MELD) scores. Materials and Methods: We used transcranial Doppler to investigate the cerebral hemodynamic parameters, namely the mean flow velocity of the middle cerebral artery, pulsatility index (PI), and resistive index (RI), in 50 patients who had decompensated cirrhosis and in a control group of 50 healthy people. We also investigated their relationship to the Child–Pugh and MELD scores. Results: Patients with cirrhosis had a lower mean flow velocity than those in the control group. Further, patients with cirrhosis had higher PI and RI values. There was a positive correlation between PI and the Child–Pugh score. In addition, there was a positive correlation among PI, RI, and the MELD score. The RI values of patients with ascites were higher than those of patients without ascites. Conclusion: Cerebral autoregulation might be impaired in patients with cirrhosis. Cerebral resistance proportionally increases to disease severity. There was a positive correlation among PI, RI, and MELD scores, which means that transcranial Doppler might be useful not only in the follow-up of the severity of the disease but also in determining the survival of these patients.